2020
DOI: 10.2174/1570159x18666200128120729
|View full text |Cite
|
Sign up to set email alerts
|

OMEGA-3 Interventions in Alcohol Dependence and Related Outcomes: A Systematic Review and Propositions

Abstract: Background: Pharmacological treatment for alcohol dependence has only three approved drugs: disulfiram, naltrexone and acamprosate. The effects of these drugs are, however, limited, presenting several side effects and a modestly higher efficacy compared to placebo. The administration of omega-3 might bring new perspectives to relapse prevention. Methods: This systematic review aimed to analyze the available literature, compiling the studies that used omega-3 to prevent relapse in alcohol dependents. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Three systematic reviews with a total of 20 dietary intervention studies in individuals with substance use disorders were included. 26,83,84 Two reviews were published in 2020 83,84 and one in 2021, 26 and all included studies with adult populations. Figure 4 depicts the search dates of the reviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three systematic reviews with a total of 20 dietary intervention studies in individuals with substance use disorders were included. 26,83,84 Two reviews were published in 2020 83,84 and one in 2021, 26 and all included studies with adult populations. Figure 4 depicts the search dates of the reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 depicts the search dates of the reviews. Two reviews focused on individuals with alcohol use disorder, with Galduroz et al including studies of omega‐3 supplementation, 83 and McLean et al including any nutrition intervention 84 . Whatnall et al focused on any nutrition intervention in adults with substance use disorders for illicit substances or illicit use of pharmaceutical substances 26 .…”
Section: Resultsmentioning
confidence: 99%
“…improvements in preclinical studies at the behavioral, cellular, and molecular level (6). Instead, a narrative review suggested that the ingestion of the omega-3 metabolite, docosahexaenoic acid (DHA), in childhood and adolescence has an important role in the neurodevelopment of the prefrontal cortex, an area involved with impulse control, contributing to decrease vulnerability to alcohol dependence (28).…”
Section: Discussionmentioning
confidence: 99%
“…Polyunsaturated fatty acids (PUFAs), mainly ômega-3 and ômega-6, are being studied as a possible adjuvant in alcoholism disorders treatment (6). In an animal model, ômega-3 reduced anxiety-like behaviors in newborn rats that previously received ethanol (7).…”
Section: Introductionmentioning
confidence: 99%
“…[1] AD has a high recurrence rate without an effective treatment. [2] However, targeted interventions can play a positive role in preventing relapse based on the investigation and analysis of high-risk factors that cause patients with AD to relapse. [3] AD treatment includes routine treatment and psychological rehabilitation.…”
Section: Introductionmentioning
confidence: 99%